Prophecy, Protest and Public Theology: The Relevance of Dietrich Bonhoeffer’s Prophetic Mandate in Today’s Post-truth World - Searle, Joshua T. ca. 21. Jh. (Journal of European Baptist Studies, 2020)
German pastor, theologian and martyr, Dietrich Bonhoeffer (1906-1945), maintained that in situations of rampant injustice, Christians are commanded by Christ to love their neighbour by taking a stand against evil. Bonhoeffer’s life and legacy remind us that Christian compassion is obliged to express itself in protest, active resistance and civil disobedience — in other words, by ‘putting a spoke in the wheel of injustice’. In this article I will explore how Bonhoeffer’s life and legacy can help Christians to discover their public witness to the world in terms of prophetic protest.